2020
DOI: 10.1115/1.4046268
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thermomechanical Stresses in Double-Wall Effusion Cooled Systems

Abstract: In this study, thermal stresses in a double-wall cooling system are analyzed. We consider an infinite flat double-wall geometry and assume that it can be represented by an axisymmetric unit cell, wherein the thermal loadings and deformation at the boundaries are determined by periodicity conditions. A thermal model is initially developed to obtain the thermal fields using a combination of empirical correlations and computational fluid dynamics (CFD) analysis. The thermal fields are then analyzed such that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…For critical engine hot stage components, such as conventional turbine rotor blades, the major importance of thermal stresses over mechanical (centrifugal/inertial) stresses [25][26][27] and aerodynamic bending (gas bending) stresses has been shown [4,22,28]. However, information for non-conventional double wall configurations is limited to the reports by Murray et al [4], Elmukashfi et al [29] and the recent work by the authors [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For critical engine hot stage components, such as conventional turbine rotor blades, the major importance of thermal stresses over mechanical (centrifugal/inertial) stresses [25][26][27] and aerodynamic bending (gas bending) stresses has been shown [4,22,28]. However, information for non-conventional double wall configurations is limited to the reports by Murray et al [4], Elmukashfi et al [29] and the recent work by the authors [20].…”
Section: Introductionmentioning
confidence: 99%
“…The study identified that significant thermal stresses mainly arise by a temperature gradient through the thickness of the outer wall as well as by the average temperature difference between the two walls which are mechanically coupled by the pedestals. The latter was studied in more depth by Elmukashfi et al [29] who derived both FE and plate theory solutions for 2D and axisymmetric flat double wall geometric idealisations, that described the nature of the thermal stress field as a function of geometry. The sensitivity of thermal stresses as a function of primary geometric features, temperature field perturbations as well as heat transfer, coolant flow constants i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The merit of the approach is that it allows for a rapid evaluation of the film effectiveness and blade external temperature distributions as well as of the coolant mass flow consumption. Elmukashfi et al [32] explored the thermoelastic stress field in simple double wall elements, including the effect of cooling parameters, i.e. Re and Biot number, and perturbations of the temperature field, on peak stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the aerothermal aspects of DWTC, systematic studies of the mechanical performance is limited to a few recent studies [12,[32][33][34], mainly conducted by the authors. These studies indicate that DWTC systems can experience severe thermal stresses [34] as significant stress concentration factors (SCF) occur at holes and pedestals [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, metal effectiveness and mechanical stresses should be considered for a better understanding of the overall consequences on more engine-like designs. This is an area of research investigated by Elmukashfi et al [21], and something that the authors of this study look to expand upon.…”
Section: Discussionmentioning
confidence: 86%